Studying the effect of the genotypes of the GH gene on blood parameters and some structural characteristics of Iraqi buffalo milk - Meitham K, Ali AL-Galiby; Mazen Majed Malbas Al-Hasnawi (University of Thi-Qar Journal of agricultural research, 2022)
The samples of this study were collected from the private fields of buffalo breeders in the Al-Tar district of Dhi Qar Governorate / Karma Bani Said district, where 50 samples of milking female buffaloes were used in the experiment, with ages ranging from (2-3 years), this study was conducted in the laboratories of the College Agriculture and Marshes Department of Animal Production for the period from 15/11/2021 to 30/5/2022 with the aim of diagnosing the genetic morphology of the growth hormone gene in Iraqi buffaloes and its relationship to blood parameters and some characteristics of milk composition. Where the blood parameters measurements included the number of red blood cells, the number of white blood cells, the percentage of hemoglobin in the blood and the volume of the aggregated cells. As for the measurement of milk components, it included protein percentage, lactose sugar percentage, fat percentage, percentage of non-fat solids, milk density, freezing point, ash percentage and water percentage. Then DNA was extracted from animal blood samples in the Molecular Genetics Laboratory of For the Marshes Research Center / Dhi Qar University, the primer of the growth hormone gene was amplified and then the genotypes in the growth hormone gene were determined using (PCR) technique by electrophoresis with a relay device, and then the sequence of bases was analyzed using the sanger sequencing technique. And then study the relationship between the genetic structures and the traits mentioned above. The results of the polymerase chain reaction (PCR) analysis of the growth hormone gene showed the appearance of a bundle with a size of 1196 base pairs, and the appearance of two alleles, G and T, where their frequency was (0.64 and 0.36), respectively, and by three genotypes: GG, TT and GT, where the frequency of these structures reached genetic (0.60, 0.32 and 0.08), respectively. Whereas, the value of chi-square was 17.1, which indicates the mismatch of the observed and expected animals, which indicates the imbalance of the population, which was observed in the study from the genetic frequencies of the unbalanced population. A single silent mutation was also found at position 118 of the 1196-base-pair-long studied region in the non-coding region 2Intron and at site 611 of the complete gene. The results of the polymerase chain reaction (PCR) analysis of the growth hormone gene showed a bundle with a size of 1196 base pairs, and the appearance of two alleles, G and T, with three genotypes: GG, TT and GT. The appearance of a single silent mutation at position 118 of the 1196-base-pair-long studied region in the 2Intron noncoding region and at site 611 of the complete gene. The frequency of the G allele was 0.64, while the frequency of the T allele was 0.36, and the frequency of the genotypes GG, TT and GT was (0.60, 0.32 and 0.08), respectively. Whereas, the value of chi-square was 17.1, which indicates the mismatch of the observed and expected animals, which indicates the imbalance of the population, which was observed in the study from the genetic frequencies of the unbalanced population. Through the obtained results, it was found that the red blood cells, the hemoglobin percentage and the volume of the compacted cells were not affected by the genotypes, as the highest value of the red blood cells was recorded by the GT genotype, which was (7.11 ± 0.69) * 106 cells/ml. Whereas, the GG genotype recorded the highest value for both hemoglobin and the volume of packed blood cells (13.022 ± 2.076) g/dL and (40.07 ± 6.23)%, respectively. As for white blood cells, they were significantly affected (P < 0.05) by genotypes, where the GT genotype was superior to the two genotypes GG and TT, and its value was (a 9.225 ± 0.317) * 103 cells/ml. Also, the composition of milk was not affected by the different genotypes of the growth hormone gene, where the highest value of the degree of freezing and milk density was recorded by the GT genotype, as its value was (0.430 ± 0.025) m5 and (27.400 ± 2.540) g/cm3, respectively. While the GG genotype recorded the highest value for lactose, protein and non-fat solids (5.180 ± 1.302, 3.398 ± 0.141 and 18.138 ± 2.322)%, respectively. As for the percentage of fat, ash and water, the highest value was recorded in the TT genotype (7.608 ± 2.027, 2.596 ± 0.284 and 81.868 ± 1.531) %, respectively.